Food insecurity and physical functioning in Boston area Puerto Rican older adults. Issue 12 (5th December 2022) - Kuehl, Lillian; Lee, Jong Soo; Dinesh, Deepika; Na, Muzi; Tucker, Katherine L; Palacios, Natalia
Abstract: Objective: Prior studies have found evidence of a relationship between food insecurity and functional limitations among older populations in the USA. Design: This is a longitudinal investigation of food security in relation to functional limitations, assessed as Activities of Daily Living (ADL) and Instrumental Activities of Daily Living (IADL) scores. Setting: The Greater Boston, MA area. Participants: 1461 Boston Puerto Rican Health study participants, predominantly (70·5 %) female and aged 57·1 years (sd ± 7·6) at baseline followed for 6·2 (sd ± 0·98) years. Results: In cross-sectional analysis at baseline, participants reporting severe food insecurity had greater functional limitations (higher ADL; β = 2·34; 95 % CI (1·48, 3·19)) and higher IADL ( β = 1·17, 95 % CI (0·68, 1·65)) compared with food secure participants. In longitudinal linear mixed models, severely food insecure participants at baseline had greater functional limitations over 5 years, as assessed by ADL ( β = 1·74; 95 % CI (0·95, 2·53); P < 0·001) and IADL ( β = 0·93, 95 % CI (0·48, 1·38)) compared with food secure participants. However, baseline food security did not significantly alter the 5-year trajectory in ADL ( P -interaction between baseline food security and time for ADL and IADL = 0·41 and 0·47, respectively). Conclusions: In this cohort of Boston area Puerto Rican adults, those who are food insecure had consistently higher ADL and IADL scores over time, compared with those who are food secure. Baseline food security did not appear to alter the trajectory in ADL or IADL score.